2019
DOI: 10.1186/s13643-019-1181-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening for thyroid dysfunction and treatment of screen-detected thyroid dysfunction in asymptomatic, community-dwelling adults: a systematic review

Abstract: BackgroundThis systematic review was conducted to inform the Canadian Task Force on Preventive Health Care recommendations on screening for thyroid dysfunction (TD). The review sought to answer key questions on the benefits and harms of screening for TD, patients’ values and preferences for screening, and the benefits and harms of treating screen-detected TD.MethodsThis review followed Canadian Task Force on Preventive Health Care methods, which include the Grading of Recommendations Assessment, Development, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 64 publications
2
30
0
4
Order By: Relevance
“…Therefore, the results from these studies have not resolved the debate as to the appropriateness of treatment in subjects with SCH. Some of the reasons for this debate are new findings showing a shifting of normal TSH values to higher levels with the advancement of age 15,54‐59 . The problem with deciding treatment for patients with SCH are the changes in the circadian rhythm of thyroid hormones and their normal reference values based on age, sex, race, ethnicity and time of day the blood sample is drawn 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results from these studies have not resolved the debate as to the appropriateness of treatment in subjects with SCH. Some of the reasons for this debate are new findings showing a shifting of normal TSH values to higher levels with the advancement of age 15,54‐59 . The problem with deciding treatment for patients with SCH are the changes in the circadian rhythm of thyroid hormones and their normal reference values based on age, sex, race, ethnicity and time of day the blood sample is drawn 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several other studies have also shown that age, sex, ethnicity, iodine status, BMI, reproductive status and assay method are independent factors that modify the TSH range 61‐64 . All these factors contribute to the uncertainty of treatment of SCH and a recent large review and meta‐analysis found no credible evidence that treatment of patients with SCH, especially in older individuals was not beneficial, and therefore, is not indicated and it could cause adverse CV effects including cardiac arrhythmias 57 . Also, controversial statements from some studies that “subclinical hypothyroidism is a mild thyroid failure and should be treated”, 65 and from other that “the treatment of subclinical hypothyroidism is seldom necessary”, 66 make the decision to treat or not to treat these patients difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation is based on systematic reviews 17 on the effectiveness (i.e., benefits and harms) of screening for thyroid dysfunction in asymptomatic, nonpregnant adults; the effectiveness of treating screen-detected thyroid dysfunction in asymptomatic, nonpregnant adults; and patient values and preferences related to screening (see analytic framework, Appendix 1, available at www. cmaj.ca/lookup/suppl/doi:10.1503/cmaj.190395/-/DC2).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol (PROSPERO: CRD42016033622), systematic reviews 17 and draft guideline were externally peer reviewed. Two clinical experts engaged with Public Health Agency of Canada staff to address technical and clinical considerations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation